Muhammadiyah's Educational Philanthropy Movement in North Kolaka - Muhammad Alifuddin; Suarni Suarni; Nurjannah Nurjannah (Shautut Tarbiyah, 2020)
This study aims to provide an analytical view of the Muhammadiyah Education Philanthropy Movement in North Kolaka. The research data was obtained through a series of in-depth interviews, observations and document studies. All data obtained was assessed in stages using the Miles and Huberman analysis models.Based on data’s found in the field of research, the Muhammadiyah educational philanthropy movement has existed in this region since 1968. The Muhammadiyah philanthropy movement in North Kolaka is a social fact that is inevitable to be appreciated. Imagine, the movement of social movements has been present in a social space that was historically geographically isolated and prone to historically political politics. In such limited conditions, in a period where the eyes of social movements are generally still "quiet" asleep and while the hands of devotion are still rigidly grasped, Muhammadiyah with all its limitations greets the hopes of rural children who are far from educational services, in order to provide formula of literacy as the solution to the thirst for education that they feel and never felt before.Muhammadiyah's ability to fulfill literacy expectations for a number of rural children during the period of education scarcity in North Kolaka which continues to this day, such a nice result of collective sincerity after all. The construction of collective excitement is channeled philanthropically by the Muhammadiyah community on the foundation of humanitarian principles that are rahmatanlilalamin, with one common goal, namely; enrich the life of a nation. These efforts in the political context can be interpreted as wordless nationalism, which is very rarely filtered through proclamation but lives in reality.Keywords: Philantrophy, Education and Muhammadiyah